KORELASI ANTARA KETERLIBATAN AKADEMIK DENGAN PRESTASI BELAJAR SISWA KELAS X DI SMK NEGERI 1 KOTA BENGKULU - Dharmayana, I Wayan; Shinta, Lenny Alvera (UNIB Press, 2019)
ABSTRACTThis study aimed to describe empirically Relationship Between Academic Engagement With Student Achievement In Class X SMK N 1 Bengkulu. Population in this study is class x students of SMK N 1 Bengkulu 2013-2014 school year with 353 students. The sampling technique used is simple random sampling and obtained samples of 83 students. Data Academic Engagement in this study taken with questionnaire, whereas for learning achievement and intelligence taken using methods of documentation. Validity of the instruments test using Product Moment Correlation which then results are correlated with whole-part technique and reliability testing instruments using Cronbach Alpha. From the data processing with partial correlation analysis correlation coefficient obtained for rx1.y-x2 = 0,422 (p<0,05). It can be concluded that there is a positive relationship and significantly between academic engagement and student achievement.Keyword : Academic engagement, academic achievement, intelligence